Impacted Tooth: A Cause of Odontogenic Lesion in the Jawbones - Gayatri Potukuchi (Indian Journal of Forensic Medicine & Toxicology, 2020)
The dentigerous cyst is the commonest developmental odontogenic cyst encountered in the jawbonesaccounting for about one-fourth of all reported cases. As with other cysts, they present as asymptomaticlesions that are either detected on routine radiographs or when they cause swelling leading to facialasymmetry. Since the cyst is associated with an impacted tooth, the common teeth involved are impactedmandibular third molars or maxillary canines. This paper isan overview of the impacted tooth, which can bea cause of odontogenic lesion in the jawbones